Molecular dynamics study on membrane fouling by oppositely charged proteins - Ma, Yuanqiao (2022)
Membrane fouling continues to hamper the performance of membrane-filtration processes. A challenge with macromolecular foulants like proteins is that macroscopic characterizations, like net electrical charge, may be poorly correlated with membrane fouling. This necessitates a molecular-scale analysis of the local interactions. In this study, molecular dynamics simulations have been performed to understand the interactions between two similar-sized proteins with opposite overall charges (namely, lysozyme and α-lactalbumin) and a negative-charged membrane. Surprisingly, the protein–membrane distances and adsorption probabilities of both proteins are similar. Compared with the positive-charged lysozyme, the negative-charged α-lactalbumin exhibits (a) greater protein–membrane attractive interaction energy due to synergy among adsorption sites; (b) lower root-mean-squared deviations (RMSD); and (c) greater number of residues that show low root-mean-squared fluctuations (RMSF). These results indicate that local interactions are critical and thus highlight the pitfall of using the overall protein characteristics as predictors of membrane fouling.